The political economy of coal in Poland: Drivers and barriers for a shift away from fossil fuels - Hanna Brauers; Pao-Yu Oei (Energy Policy, 2020)
Poland is the largest hard coal and second largest lignite producer in the EU, generating around 80 percent of its electricity from coal. Resistance to a reduction in coal production and consumption comes from various actors, namely, coal corporations, unions, parts of civil society and the government – as well as their coalitions. Their opposition centres around the prospect of losing their business, past negative experiences with structural change, fears of rising energy prices and energy security concerns, as well as potential unemployment in regions almost entirely dependent on coal. This paper identifies key political and economic drivers and barriers of a reduction in coal production and consumption in Poland using the Triple Embeddedness Framework. Uneconomic coal mining, unavoidable energy infrastructure investments, rising air pollution levels and pressure from the European Union might provide new political momentum for a shift away from coal in line with international climate targets. However, results show that to achieve political feasibility, policies targeting a reduction in coal production and use need to be implemented jointly with social and structural policy measures, addressing a just transition for the affected regions in line with the vision of a `European Green Deal'.
Keywords: 330; Poland; Coal phase-out; Energy transition; Triple embeddedness framework; Political feasibility; Political economy